2017
DOI: 10.1155/2017/7657190
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization, and Mode of Action of Pentocin JL-1, a Novel Bacteriocin Isolated from Lactobacillus pentosus, against Drug-Resistant Staphylococcus aureus

Abstract: Staphylococcus aureus and its drug-resistant strains, which threaten public health and food safety, are in need of effective control by biopreservatives. A novel bacteriocin, pentocin JL-1, produced by Lactobacillus pentosus that was isolated from the intestinal tract of Chiloscyllium punctatum, was purified by a four-step chromatographic process. Mass spectrometry based on MALDI-TOF indicated that pentocin JL-1 has a molecular mass of 2987.23 Da. Only six of the twenty-five amino acids could be identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…After incubation for 2 h at pH values from pH 2.0 to 8.0 stable activity but its activity slightly reduced at pH 10.00 and showed activity at pH 12.0 This result showed that the BLS was resistant to acid conditions (Table 4). That agreement with other research on characterized L. plantarum that inhibition zone pH treatment stable at range pH 2.0 to 8.0 (Jiang et al 2017).…”
Section: Characterization Of the Bacteriocinsupporting
confidence: 93%
“…After incubation for 2 h at pH values from pH 2.0 to 8.0 stable activity but its activity slightly reduced at pH 10.00 and showed activity at pH 12.0 This result showed that the BLS was resistant to acid conditions (Table 4). That agreement with other research on characterized L. plantarum that inhibition zone pH treatment stable at range pH 2.0 to 8.0 (Jiang et al 2017).…”
Section: Characterization Of the Bacteriocinsupporting
confidence: 93%
“…The bacteriostatic or bactericidal mode of action of IP6 was tested using a method described previously by Jiang et al [45]with some modifications. L. monocytogenes ATCC 19117, S. aureus ATCC 6538 and S. Typhimurium ATCC 14028 were cultivated in 100 mL of PALCAM, Chapman broth and xylose lysine xeoxycholate (XLD) broth, respectively.…”
Section: Mode Of Action Of Phytic Acidmentioning
confidence: 99%
“…Values with a different letter (A-E) of a same diameter inhibition zone are significantly different (P<0.05) To investigate the effects of varying IP6 dose on L. monocytogenes, S. aureus and S. Typhimurium, the bacterial growth was followed over 24 h and evaluated in comparison with the control culture (without addition of IP6), following the protocol developed by Jiang et al [45]. IP6 was added to L. monocytogenes ATCC 19117, S. aureus ATCC 6538 and S. Typhimurium ATCC 14028cells after 3 h of incubation, when growth reached the beginning of the exponential phase (cell density of about 10 6 CFU/ml).…”
Section: Assessment Of the Antibacterial Activity Of Phytic Acidmentioning
confidence: 99%
“…Glycines are often found in flexible loop regions as they do not contain a side chain, increasing the conformational flexibility (demonstrated by NMR solution structures of other circular bacteriocins) 13,28,43 . The hydrophobic core residues are Ile 1 , Ile 4 , Ala 5 , Val 10 , Leu 12 , Ala 20 , Leu 24 , Leu 30 , Val 33 , Ala 34 , Ile 37 , Leu 38 , Val 40 , Leu 42 , Ala 46 , Ala 50 and Ala 58 . All of these residues have <20% solvent exposure calculated based on GETAREA 44 .…”
Section: Crystal Structure Of Plantacyclin B21agmentioning
confidence: 99%
“…Replacing aspartic acid at position 17 with the glutamic acid strongly enhanced the antimicrobial activity of the pediocin-like bacteriocin sakacin P. This result suggests that the anionic residues interact in a structurally specific and restricted manner with a cationic region on the target cell or on the peptide itself 49 . Given that bacteriocins generally kill through disruption of proton motive force 50 or through the Grotthuss mechanism of gramicidin 51 , placement of negative charges near the pore may facilitate pore selectivity and cation flow out of the target cell by reducing the electrostatic energy profile and increasing selectivity for divalent cations such as Ca 2+ 52 . These findings suggest that anionic residues are as important as cationic residues in terms of target specificity of the bacteriocins.…”
Section: Surface Characteristics Of Circular Bacteriocinsmentioning
confidence: 99%